ENHANCING ISLAMIC FINANCIAL LITERACY IN INDONESIAN YOUTH GENERATES BROADER SOCIETAL BENEFITS: Received: 18th July 2023; Revised: 27th November 2023, 07th December 2023; Accepted: 08th December 2023 - Azra Rosadi, Anandita; Alexakis, Dr. Christos; Pratiwi Putri, Anindia (PEOPLE: International Journal of Social Sciences, 2024)
Indonesia, with a predominantly Muslim population, exhibits low levels of financial literacy and Islamic financial literacy, despite a growing interest in Islamic banking. This research focuses on evaluating the financial literacy of young Indonesians and its relationship with Islamic financial literacy policies. The quantitative approach, based on a survey of 70 respondents, reveals that the youth in Indonesia possess moderate financial literacy and Islamic finance knowledge. Government policies, primarily centered around personal learning and online education, demonstrate limited efficacy in improving financial literacy among the youth. The study suggests that the low level of Islamic financial literacy cannot be solely attributed to existing policies, as other external factors play a significant role. The research emphasizes the need for a more comprehensive understanding of the multifaceted influences on the relationship between Islamic financial literacy and societal outcomes in Indonesia.